Comparison of non-mydriatic retinal photography with ophthalmoscopy in 2159 patients: mobile retinal camera study. Issue 6763 (1st December 1990) - Taylor, R; Lovelock, L; Tunbridge, W M; Alberti, K G; Brackenridge, R G; Stephenson, P; Young, E
Abstract : OBJECTIVE--To determine whether non-mydriatic Polaroid retinal photography was comparable to ophthalmoscopy with mydriasis in routine clinic screening for early, treatable diabetic retinopathy. DESIGN--Prospective study of ophthalmoscopic findings according to retinal camera screening and ophthalmoscopy and outcome of referral to ophthalmologist. SETTING--Outpatient diabetic clinics of three teaching hospitals and three district general hospitals. PATIENTS--2159 Adults selected randomly from the diabetic clinics, excluding only those registered as blind or those in wheelchairs and unable to enter the screening vehicle. MAIN OUTCOME MEASURES--Numbers of patients and eyes correctly identified by each technique as requiring referral with potentially treatable retinopathy (new vessel formation and maculopathy) and congruence in numbers of microaneurysms, haemorrhages, and exudates reported. RESULTS--Camera screening missed two cases of new vessel formation and did not identify a further 12 but indicated a need for referral. Ophthalmoscopy missed five cases of new vessel formation and indicated a need for referral in another four for other reasons. Maculopathy was reported in 147 eyes with camera screening alone and 95 eyes by ophthalmoscopy only (chi 2 = 11.2; p less than 0.001), in 66 and 29 of which respectively maculopathy was subsequently confirmed. Overall, 38 eyes received laser treatment for maculopathy after detection by camera screening compared with 17 after ophthalmoscopic detection (chi 2 = 8.0; p less than 0.01). Camera screening underestimated numbers of microaneurysms (chi 2 = 12.9; p less than 0.001) and haemorrhages (chi 2 = 7.4; p less than 0.01) and ophthalmoscopy underestimated hard exudates (chi 2 = 48.2; p less than 0.001). CONCLUSIONS--Non-mydriatic Polaroid retinal photography is at least as good as ophthalmoscopy with mydriasis in routine diabetic clinics in identifying new vessel formation and absence of retinopathy and is significantly better in detecting exudative maculopathy.